Distance education: Discrimination in access to internet and technology of students of I and II Cycles of Basic General Education - Mejías Padilla, Viriam (2021)
This article is framed in the context of distance education, which was implemented in Costa Rica in 2020 to stop the contagion by Covid-19. The objective is to problematize the educa- tional inequality faced by those students without access to the internet and technology, which limits their right to education. In addition, the importance of establishing strategies that allow future inclusion of technological resources within educational processes is presented, so that a higher quality education can be provided and appropriate to the current context. It is concluded that access to the internet and technological resources are the first step to guarantee the right to education in the distance education modality.